(untitled) (Nativa, 2021)
O objetivo deste artigo é caracterizar o uso dos produtos florestais não madeireiros (PFNM) pelas populações ribeirinhas em comunidades na Flona Tapajós, compreendendo as questões relacionadas às principais espécies coletadas, seus usos e atribuição de valor aos produtos confeccionados. Foi realizado um Diagnóstico Rápido Rural (DRR) com os coletores de PFNMs, e entrevistas com um total de 10 artesãos. As espécies mais citadas foram: morototó, tento vermelho, tento amarelo, saboneteira, açaí, jutaí e lágrima de nossa senhora que são utilizadas na produção de artesanatos e biojóias; também se utiliza as fibras (buriti, tucumã e curuá) e as madeiras (coração de negro, itaúba, cedro, arara castanha e molongó). As biojóias variam de valor entre R2,00 a R20,00 e as peças ornamentais de madeira de R10,00 a R300,00. As principais vantagens de trabalhar com PFNM apontadas na entrevista são a facilidade de coletar sementes, o fato de ter demanda e gerar renda aos artesãos envolvidos. As dificuldades mencionadas são a coleta das sementes do morototó e paricá e o acesso as árvores na floresta. Jamaraquá, Maguari e São Domingos são exemplos bem-sucedidos de que os produtos oriundos da floresta têm mercado consolidado e são representação cultural e social dos povos da floresta. Palavras-chave: artesanato; biojóias; população tradicional; Amazônia. Use of non-wooden forest products in the National Forest of Tapajós communities ABSTRACT: The aim of this article is to characterize the use of non-timber forest products (NTFP) by riverine populations in communities in Flona Tapajós, including issues related to the main species collected, their uses and attribution of value to the manufactured products. the use of non-timber forest products (NTFP) by riverine populations in communities in Flona Tapajós, including issues related to the main species collected, their uses and attribution of value to the products made. A rapid rural appraisal (RRA) was conducted with community NTFP collectors, followed by interviews with the artisans, including a total of 10 people. The most cited species in the RRA were morototó, bead tree, tento amarelo, wingleaf soapberry, açaí palm, jutaí, and Job’s tears, which are used to produce handicrafts and bio-jewels. In addition, buriti, tucumã, and curuá fiber and lapachillo, itaúba, cedar, arara castanha, and molongó wood were used. The price of bio-jewels varies from BRL 2 to 20, and of the wood ornamental pieces from BRL 10 to 300. The main advantages of working with NTFP highlighted in the interviews were that seed collection is easy, that there is demand, and that income is generated for community members. The difficulties mentioned were the collection and processing of morototó and paricá seed, and access to trees. Jamaraquá, Maguari, and São Domingos are successful examples of forest products that consolidated the market and are cultural and social representation of the forest peoples. Keywords: handicrafts; bio-jewels; traditional population; Amazon.